# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime } = 1+2 x y
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime } = y+2 x \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+p \left (x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+p \left (x \right ) y = q \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right ) y^{\prime } = x -y
\] |
✓ |
✓ |
|
\[
{}2 x y y^{\prime } = 2 y^{2}+x^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+2 \sqrt {x y}
\] |
✓ |
✓ |
|
\[
{}\left (x -y\right ) y^{\prime } = x +y
\] |
✓ |
✓ |
|
\[
{}x \left (x +y\right ) y^{\prime } = y \left (x -y\right )
\] |
✓ |
✓ |
|
\[
{}\left (x +2 y\right ) y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{2} y^{\prime } x = y^{3}+x^{3}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = x y+x^{2} {\mathrm e}^{\frac {y}{x}}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = x y+y^{2}
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = x^{2}+3 y^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-y^{2}\right ) y^{\prime } = 2 x y
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = y^{2}+x \sqrt {4 x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+\sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime }+x = \sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x \left (x +y\right ) y^{\prime }+y \left (3 x +y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {x +y+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (y+4 x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right ) y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+2 x y = 5 y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } y^{2}+2 x y^{3} = 6 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y+y^{3}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+2 x y = 5 y^{4}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+6 y = 3 x y^{{4}/{3}}
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime }+y^{3} {\mathrm e}^{-2 x} = 2 x y
\] |
✓ |
✓ |
|
\[
{}y^{2} \left (x y^{\prime }+y\right ) \sqrt {x^{4}+1} = x
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime } y^{2}+y^{3} = {\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}3 y^{2} y^{\prime } x = 3 x^{4}+y^{3}
\] |
✓ |
✓ |
|
\[
{}x \,{\mathrm e}^{y} y^{\prime } = 2 \,{\mathrm e}^{y}+2 x^{3} {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}2 x \sin \left (y\right ) \cos \left (y\right ) y^{\prime } = 4 x^{2}+\sin \left (y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}\left ({\mathrm e}^{y}+x \right ) y^{\prime } = x \,{\mathrm e}^{-y}-1
\] |
✓ |
✓ |
|
\[
{}2 x +3 y+\left (2 y+3 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}4 x -y+\left (6 y-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2}+2 y^{2}+\left (4 x y+6 y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{2}+3 x^{2}+\left (2 x^{2} y+4 y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{3}+\frac {y}{x}+\left (y^{2}+\ln \left (x \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+y \,{\mathrm e}^{x y}+\left (2 y+x \,{\mathrm e}^{x y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right )+\ln \left (y\right )+\left (\frac {x}{y}+{\mathrm e}^{y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +\arctan \left (y\right )+\frac {\left (x +y\right ) y^{\prime }}{1+y^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} y^{3}+y^{4}+\left (3 y^{2} x^{3}+y^{4}+4 x y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x} \sin \left (y\right )+\tan \left (y\right )+\left ({\mathrm e}^{x} \cos \left (y\right )+x \sec \left (y\right )^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {2 x}{y}-\frac {3 y^{2}}{x^{4}}+\left (\frac {2 y}{x^{3}}-\frac {x^{2}}{y^{2}}+\frac {1}{\sqrt {y}}\right ) y^{\prime } = 0
\] |
✗ |
✓ |
|
\[
{}\frac {2 x^{{5}/{2}}-3 y^{{5}/{3}}}{2 x^{{5}/{2}} y^{{2}/{3}}}+\frac {\left (3 y^{{5}/{3}}-2 x^{{5}/{2}}\right ) y^{\prime }}{3 x^{{3}/{2}} y^{{5}/{3}}} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } x = y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }+{y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } x +y^{\prime } = 4 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+3 x y^{\prime } = 2
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }+{y^{\prime }}^{2} = y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \left (x +y^{\prime }\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 2 y {y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}y^{3} y^{\prime \prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 2 y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime } = 3 {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = f \left (a x +b y+c \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+p \left (x \right ) y = q \left (x \right ) y^{n}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+p \left (x \right ) y = q \left (x \right ) y \ln \left (y\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-4 x^{2} y+2 y \ln \left (y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-y+x -1}{x +y+3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 y-x +7}{4 x -3 y-18}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x -y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {y \left (-y^{3}+2 x^{3}\right )}{x \left (2 y^{3}-x^{3}\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y^{2} = x^{2}+1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y = 1+x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }-\frac {{y^{\prime }}^{2}}{4}
\] |
✓ |
✓ |
|
\[
{}r y^{\prime \prime } = \left (1+{y^{\prime }}^{2}\right )^{{3}/{2}}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = x-x^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = 10 x-x^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = 1-x^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = 9-4 x^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = 3 x \left (5-x\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = 3 x \left (5-x\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = 4 x \left (7-x\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = 7 x \left (x-13\right )
\] |
✓ |
✓ |
|
\[
{}x^{3}+3 y-x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{2}+3 y^{2}-x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y+y^{2}-x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{3}+{\mathrm e}^{x}+\left (3 x^{2} y^{2}+\sin \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 y+x^{4} y^{\prime } = 2 x y
\] |
✓ |
✓ |
|
\[
{}2 x y^{2}+x^{2} y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y+x^{3} y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+2 x y = y^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+2 y = 6 x^{2} \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+x^{2}+y^{2}+x^{2} y^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = x y+3 y^{2}
\] |
✓ |
✓ |
|
\[
{}6 x y^{3}+2 y^{4}+\left (9 x^{2} y^{2}+8 x y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}4 x y^{2}+y^{\prime } = 5 y^{2} x^{4}
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime } = x^{2} y-y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 y = 3 x^{2} {\mathrm e}^{-3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-2 x y+x^{2}
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x}+y \,{\mathrm e}^{x y}+\left ({\mathrm e}^{y}+x \,{\mathrm e}^{x y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y-x^{3} y^{\prime } = y^{3}
\] |
✓ |
✓ |
|
\[
{}3 x^{5} y^{2}+x^{3} y^{\prime } = 2 y^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+3 y = \frac {3}{x^{{3}/{2}}}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime }+\left (x -1\right ) y = 1
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 6 y+12 x^{4} y^{{2}/{3}}
\] |
✓ |
✓ |
|